2021
DOI: 10.31557/apjcp.2021.22.11.3607
|View full text |Cite
|
Sign up to set email alerts
|

Opuntiol Inhibits Growth and Induces Apoptosis in Human Glioblastoma Cells by Upregulating Active Caspase 3 Expression

Abstract: Background: Glioblastoma Multiforme (GBM) is a deadly tumor with poor prognosis. Resistance to apoptosis considered as an important factor in treatment failure. Therefore, identification of new compounds that facilitates apoptosis is crucial. Natural Anti-inflammatory compounds have emerged as potential anti-cancer agents and should be explored for their apoptotic activity against GBM. Therefore, the present study aims to evaluate growth inhibitory and apoptotic activity of a natural anti-inflammatory compound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The cells were kept in incubator with humidified atmosphere at 37 0 C and 5% of carbon dioxide (CO 2 ). 17 The 3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay was used to analyse the effect of test compounds on percentage inhibition of growth in the cells. Briefly, mono-layer of the cells in the flask was trypsinised using trypsin and ≈3000 cells/100μL of complete media was dispensed in 96-well plates.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The cells were kept in incubator with humidified atmosphere at 37 0 C and 5% of carbon dioxide (CO 2 ). 17 The 3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay was used to analyse the effect of test compounds on percentage inhibition of growth in the cells. Briefly, mono-layer of the cells in the flask was trypsinised using trypsin and ≈3000 cells/100μL of complete media was dispensed in 96-well plates.…”
Section: Methodsmentioning
confidence: 99%
“…The percentage of growth inhibition was determined by the formula: % growth inhibition of cells = 100-[(At -Ab)/ (Ac -Ab)] *100. 17 The half-maximal inhibitory concentration (IC50) was computed by the equation:…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…While the search for alternate therapeutic strategies to alleviate glioma pathogenesis is underway, previous studies had suggested that the overall prognosis in glioma patients can be improved by repurposing lead compounds of synthetic and natural origin, which, in turn, would improve the therapeutic efficacy of TMZ [5][6][7]. These therapeutic regimes, as adjuvants to the standard drug, can hamper glioma progression via modulation of signaling pathways with tolerable side effects [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…While the search for alternate therapeutic strategies to alleviate glioma pathogenesis is underway, previous studies had suggested that the overall prognosis in glioma patients can be improved by repurposing lead compounds of synthetic and natural origin, which in turn, would improve the therapeutic efficacy of TMZ (Xiao et al 2016; Ashfaque et al 2021; Precilla et al 2022). These therapeutic regimes, as adjuvants to the standard drug, can hamper glioma progression via modulation of signalling pathways with tolerable side effects (Kim et al 2010; Lu et al 2012; Wang et al 2016; Sargazi et al 2021).…”
Section: Introductionmentioning
confidence: 99%